A Prophetic Law Perspective on Judicial Independence of the Indonesian Constitutional Court: Looking Back on 20 Years - Perdana, Muhammad Anugerah; Al Faruq, Muhammad Hamzah; Ruhpinesthi, Garuda Era (Universitas Islam Indonesia, 2024)
This research analyzes the pattern of Constitutional Court judicial reviews decisions in the last 20 years since its establishment against Islamic populism cases. This research applies legal normative methodology by conducting a literature review based on secondary data analysis and case study approach. This research concludes that, first, the Constitutional Court in Indonesia is inseparable from the influence of Islamic populism which is proven by the existence of 4/7 decisions that fulfilled the variable on the characteristics of populist decisions. Apart from the strong relationship between the state and religions, this is also coupled with the weakness of procedural law. The Constitutional Court opens the space for strengthening populism in influencing the Constitutional Court decisions. Second, the fading independence of the Constitutional Court may pose a danger to democracy, including to the human rights of minority communities and may eliminate the implementation of plural constitutionalism. Also, various international literature in the last five years shows us the Constitutional Courts have tendencies to challenge the rising of Populist Movement policies made by the Government through judicial review cases. Compared to the other countries, populist movement in Indonesia became a unique phenomenon due to the high influence of Islamic identity in the judges. Not only that, but the recent cases also show the institution more favoring the populist policies made by the government than protecting minority rights.